Construing and Implementing Systems Thinking in the Study of Process Risk Management - Karpe, Rohan Jayant (Curtin University, 2016)
Systems thinking is widely recognised as a core competence for professional engineering practice. Existing engineering education literature, however, provides scant guidance on practical matters of its pedagogy, assessment, and evaluation in classroom contexts within specific engineering disciplines and units. In this thesis, using a hermeneutic-narrative inquiry approach, I offer a practical framework by which systems thinking can be suitably construed and implemented in the study of Process Risk Management.